An Assessment of Prostitution among African Women in the Diaspora: Evidence from Amma Darko’s Beyond the Horizon - Samuel Ohene Anane; Edward Owusu; Priscilla Appiah; Nana Agyemang Opoku; Bernice Quampah; Hagar Ampomah Donkor (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
The development of every nation is highly dependent on the success of the individuals in it. This is but a realization of the adage that the average man if rationally organized, lives by the sweat of his brow. Every individual becomes successful based on the work he/she does. This is to say that the individual's success and the development of a nation are mutually dependent. The African woman’s engagement in prostitution as a livelihood has attracted all forms of dialogue, both in Africa and in the diaspora. The purpose of this study was to analyse how Amma Darko presents prostitution among African women in the Diaspora. To achieve this objective, we used Beyond the Horizon as their primary source of data. We analysed the factors that push women into prostitution in the Diaspora as well as the presentation of the practice of prostitution, as presented by the primary source. The findings of the study affirmed that women who go into prostitution in the diaspora are mostly blackmailed and coerced into it by their male benefactors who take them abroad. The study also revealed that through prostitution, women sex workers get addicted to drugs, and coming out of this trade becomes almost impossible. Based on the analysis, we conclude that the expectations of the families of the sojourning African women remain a strong influence on the women joining the sex industry.